(untitled) (World Bulletin of Social Sciences, 2022)
This article examines the issues of creating effective components of vermiculite slab, thermal insulation, sound-absorbing, refractory ultralightweight concrete with functional properties obtained on the basis of foamed vermiculite and studying their properties